2013
DOI: 10.1111/peps.12047
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on Age‐Diversity Climate: The Impact of Age‐Inclusive HR Practices on Firm‐Level Outcomes

Abstract: This study investigates the emergence and the performance effects of an age-diversity climate at the organizational level of analysis. Building upon Kopelman and colleagues' (Kopelman, Brief, & Guzzo, 1990) climate model of firm productivity as well as Cox's (1994) interactional model of cultural diversity, we hypothesize a positive influence of ageinclusive HR practices on the development of an organization-wide agediversity climate, which in turn should be directly related to collective perceptions of social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
277
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 291 publications
(285 citation statements)
references
References 113 publications
(208 reference statements)
3
277
0
5
Order By: Relevance
“…Drawing on social exchange theory, we show that organisations signal that they value and care for their employees by introducing the principles of age diversity management in appraisal and compensation policies and practices, which in turn contributes to organisational performance as perceived by HR managers as well as employee productivity measured with objective data. This notion is in line with results from Boehm, Kunze, and Bruch (2014) who find a positive relationship between age-inclusive HR practices and organisational performance, mediated by employees' perceptions of social exchange. Transferring these findings to general diversity management, future studies could integrate employee welfare as a mediator in order to understand how diversity management translates into organisational performance (Guillaume et al, 2014).…”
Section: Theoretical Implicationssupporting
confidence: 85%
“…Drawing on social exchange theory, we show that organisations signal that they value and care for their employees by introducing the principles of age diversity management in appraisal and compensation policies and practices, which in turn contributes to organisational performance as perceived by HR managers as well as employee productivity measured with objective data. This notion is in line with results from Boehm, Kunze, and Bruch (2014) who find a positive relationship between age-inclusive HR practices and organisational performance, mediated by employees' perceptions of social exchange. Transferring these findings to general diversity management, future studies could integrate employee welfare as a mediator in order to understand how diversity management translates into organisational performance (Guillaume et al, 2014).…”
Section: Theoretical Implicationssupporting
confidence: 85%
“…In particular, we argue that the psychographic measure (Teuscher, 2009) of average work-related meaning is only relevant for the average relative subjective age within a company if age-inclusive HR practices support it. Age-inclusive HR practices are specific HR management practices, which ensure that all employees irrespective of their age develop their knowledge skills and abilities, become equally motivated, and receive the same opportunity to contribute to organizational goals (Boehm et al, 2014). Researchers have shown that such HR practices are related to organizational performance through a positive age-diversity climate as a mediator (Boehm et al, 2014).…”
Section: The Moderation Of Age-inclusive Hr Practicesmentioning
confidence: 99%
“…First, we review the current wisdom on diversity climate, focusing on field studies wherein general diversity climate was the focal construct. Because general climate has been the predominate subject of diversity climate work, we did not review work on diversity climates targeted toward specific demographic categories such as gender (King, Hebl, George, & Matusik, 2010) or age (Bo¨hm, Kunze, & Bruch, 2014). During the review, we sort studies by levels of analysis, as diversity climate has been studied at the individual (i.e., employee level) and aggregate levels (e.g., business unit, workgroup, and firm levels).…”
mentioning
confidence: 99%